DEVELOPMENT OF AN ANTI-MOSQUITO SPRAY GEL FORMULATION FOR A COMBINATION OF MARIGOLD FLOWERS (TAGETES ERECTA L.) AND CHRYSANTHEUM FLOWERS (CHRYSANTHEMUM INDICIUM L.) - Mulder, Keysia Stephanie Tesalonica; Mokosuli, Yermia Semuel; Lawalata, Helen Joan (Jurnal Review Pendidikan dan Pengajaran, 2024)
Mosquitoes are vectors of infectious diseases that must be controlled. One of the efforts to control mosquito vectors is by using anti-mosquito products, including anti-mosquito gel spray. Most anti-mosquito products are composed of chemicals that are harmful to health and the environment, so alternative anti-mosquito products made from natural ingredients are needed. The aim of this research is to determine an effective anti-mosquito gel spray formula from a combination of marigold flowers and chrysanthemum flowers. This research uses experimental methods to find the most effective gel spray formulation from different percentages of marigold and chrysanthemum flowers. The variations used are 0%, 2.5%, 5% and 10%. Tests were carried out using 30 adult female mosquitoes. The results obtained through the extraction of marigold flowers showed a yield of 8.922% and a yield of chrysanthemum flowers of 4.560%. The organoleptic test carried out on 10 panelists showed that on average the panelists thought they liked (in the range 4-5) their preference for color and aroma. , texture and reaction after 10 minutes of using the gel spray. The pH test showed that the four gel spray formulas had a pH of 6 or neutral. The results of the homogeneity test carried out with a glass object showed that the four gel spray formulas were homogeneous. The protective power of the 2.5% gel spray formula is 18.01%; gel spray formula 5% is 66.29% and gel spray formula 10% is 88.61%. From these results, it can be seen that a formula with a concentration of marigold and chrysanthemum flower extracts of 10% can be the most effective anti-mosquito gel spray. It is hoped that the results of this research will be useful for society in terms of using mosquito repellent that is environmentally friendly and safe for health.